(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article is dedicated to the current problem of determining the one-repetition maximum (1RM) in strength-oriented fitness programs. This topic is of particular importance in modern conditions, where there is a need to train competent fitness professionals, and the fitness industry is developing through the introduction of new business models, such as low-cost clubs and online fitness schools, where the qualifications of trainers and the quality of services are critical. The purpose of this research is to analyze and systematize existing methods for determining 1RM, as well as to provide scientifically-based recommendations to fitness professionals for optimizing the training process and minimizing injury risks for clients. The research is based on the analysis, generalization, and systematization of data from current scientific and methodological literature, as well as on a comparative analysis of various 1RM determination methods according to criteria of accuracy, safety, and practicality of application. The article details the direct 1RM testing method, which is considered the "gold standard" for accuracy, yet is associated with significant stress on the body, is time-consuming, and has a number of contraindications, especially for beginners and individuals with medical limitations. Particular attention is given to indirect methods of 1RM assessment, which are a safer and more practical alternative. The use of predictive equations (e.g., Epley, Brzycki) based on performing exercises with submaximal loads to failure (nRM) is analyzed, emphasizing the dependence of accuracy on the number of repetitions (optimally 3-6 RM) and the absence of a universal equation. The application of Rating of Perceived Exertion (RPE) and Repetitions in Reserve (RIR) scales as tools for assessing intensity and autoregulating the training process is also considered, taking into account their subjectivity and dependence on the athlete’s experience. It is concluded that the choice of 1RM determination method by a fitness trainer should be individualized, considering the client’s characteristics, with a combination of indirect approaches often being optimal.